Histopathological Changes in Some Internal Organs Of White Mice Due To Treatment With Pentoxifylline - Hassan, Salema L . (The Iraqi Journal of Veterinary Medicine, 2011)
The aim of the study was to make knowledge on the histopathological changes in some internal organs ( liver, kidney and spleen) of albino mice after treatment with therapeutic dose(16mg/kg BW/day) of pentoxifylline (PTX). Thirty albino mice which are approximately at same age (8week) and body weight were, randomly divided into three equal groups, group 1:Received tape water along the period of experiment and considered as a control group, Group 2:Treated with Pentoxifylline ( 16 mg /kgBW/day)for 30 days Group 3:Treated with Pentoxifylline ( 16 mg/kgBW/days)for 60 day. The histopathological findings of liver, kidney and spleen, showed infiltration of mononuclear cells within the liver parenchyma and portal areas and in the interstitial tissue of the kidney with perivascular lymphocytic cuffing and mild degenerative changes represented by acute cellular swelling of hepatocytes and epithelial cells lining the cortical renal tubules in addition to congestion of blood vessels Spleen showed lymphoid hyperplasia of white pulp with congestion and infiltration of lymphocytes in red pulp.